Effect of Planned Teaching on Knowledge of Mothers Regarding Prevention of Vitamin A Deficiency among Under Five Children from a Selected Urban Area - Kumbhar, Vandana (Innovational: Journal of Nursing and Healthcare, 2024)
Introduction: Vitamin A is an essential micronutrient. It enhances children’s immunity and protects against illness/morbidity and reduces death/mortality. Therefore, it is essential for child survival. Objective: The aim of the study was to assess the knowledge of mothers on Vitamin A requirements, sources, deficiency, and its prophylaxis among under five children before and after planned teaching program. Methodology: The data were collected from 100 mothers of under five children using semi structured questionnaire in the selected Anganwadi from Ahmed Nagar District. Results: The majority of the mothers belong to the age group of 21–40 (83%) and (41%) completed secondary education, Majority (58%) had two children. The knowledge mean score in pretest in the area of concept of Vitamin A was 1.78, whereas in post-test, it was increased to 3.39. Mean score analysis is done in different sections of questionnaire such as Sources of Vitamin A, requirement of Vitamin A and Vitamin A deficiency, and prevention and prophylaxis, and its found increased in post-test score in all respective areas. The overall mean score was 13.8 out of maximum score of 50 in pre-test and 31.8 in post-test which was statistically significant. Conclusion: As study shows the significance of the difference between pre-test and post-test 13.81–31.8, respectively.